The cross-linking agent hexamethylphosphoramide predominantly induces intra-locus and multi-locus deletions in postmeiotic germ cells of Drosophila. - Aguirrezabalaga, I.; Nivard, M.J.; Comendador, M.A.; Vogel, E.W. (Genetics, 1995)
The nature of DNA sequence changes induced by the cross-linking agent hexamethylphosphoramide (HMPA) within and in the vicinity of the vermilion locus of Drosophila melanogaster that produce a vermilion mutant phenotype was analyzed after exposure of postmeiotic male germ cells. Mutagenized males were mated to either females wild-type (exr+) for nucleotide excision repair (NER) or to females having a deficiency (exr-) for NER. Rearrangements, mostly deletions, represented by far the most frequent type of mutational events induced by HMPA that are detected as vermilion mutations. In the exr+ group, all but one (a double substitution) of 21 mutants characterized were large sequence changes: we found 5 intra-locus deletions, 3 intra-locus deletions associated with insertions and 12 multi-locus deletions. When taken together, deletions and deletion/insertion mutations represent 96% of the HMPA-induced DNA modifications obtained under proficient repair conditions. Of the 10 mutants obtained from crosses with exr- females, 6 intra-locus and 2 multi-locus deletions were found, as opposed to just 1 point mutation and 1 double substitution. The "hypomutability effect" observed with exr- genotypes in relation to the wild type seems to be caused by a decrease in the frequency of multi-locus deletions in the former group. The results suggest that the NER system is involved in the generation of multi-locus deletions, whereas intra-locus deletions appear to be formed through a postreplication slipped-misrepair pathway. It is concluded that an eukaryotic in vivo system with no limitations for the recovery of multi-locus deletions, such as vermilion, should be used for the analysis of DNA damage induced by cross-linking agents.